Automation, Protection and Control of Substation Based on IEC 61850 - Kumar, Shantanu (Curtin University, 2023)
Reliability of power system protection system has been a key issue in the substation operation due to the use of multi-vendor equipment of proprietary features, environmental issues, and complex fault diagnosis. Failure to address these issues could have a significant effect on the performance of the entire electricity grid. With the introduction of IEC 61850 standard, substation automation system (SAS) has significantly altered the scenario in utilities and industries as indicated in this thesis.